Assessment of river water infiltration conditions based on both chloride mass-balance and hydrogeological setting: the Krajkowo riverbank filtration site (Poland) - Gorski, Jozef; Dragon, Krzysztof; Kruc-Fijalkowska, Roksana; Matusiak, Magdalena (Geologos, 2021)
In the present work measurements of chloride concentrations were used to assess the variability of infiltration conditions and contributions of surface water and local groundwater to the discharge of wells at Krajkowo riverbank filtration site (western Poland). Tests were performed on samples from 26 wells located in a well gallery close to the River Warta. Due to higher chloride concentrations in river water in comparison with local groundwater, significant differences in concentrations in samples from individual wells were noted. In particular, lower chloride concentrations in 11 wells were recorded, which can be linked to the local occurrence of low-permeability deposits in the superficial zone; a locally higher degree of riverbed sediment clogging in the highly convex meandering zone, where strong erosion of the riverbed occurred, which in turn led to increased clogging; the occurrence of a more intensive groundwater inflow into the river valley due to water infiltration from a smaller river entering the River Warta valley, as well as unfavourable conditions for the infiltration of surface water to the lower part of the aquifer with a greater thickness. Differences in chloride concentrations observed were also used to quantify approximately river water contribution to the well production. The average contribution of the River Warta to the recharge of the entire well gallery was estimated at 59.8%.